Regulatory Mechanisms of Baicalin in Cardiovascular Diseases: A Review - Xin, Laiyun; Gao, Jialiang; Lin, Hongchen; Qu, Yi; Shang, Chang; Wang, Yuling; Lu, Yingdong; Cui, Xiangning (Frontiers in Pharmacology, 2020)
Cardiovascular diseases (CVDs) is the leading cause of high morbidity and mortality worldwide, which emphasizes the urgent necessity to develop new pharmacotherapies. In eastern countries, traditional Chinese medicine Scutellaria baicalensisGeorgi has been used clinically for thousands of years. Baicalin is one of the main active ingredients extracted from Chinese herbal medicine S. baicalensis. Emerging evidence has established that baicalin improves chronic inflammation, immune imbalance, disturbances in lipid metabolism, apoptosis and oxidative stress. Thereby it offers beneficial roles against the initiation and progression of CVDs such as atherosclerosis, hypertension, myocardial infarction and reperfusion, and heart failure. In this review, we summarize the pharmacological features and relevant mechanisms by which baicalin regulates CVDs in the hope to reveal its application for CVDs prevention and/or therapy.